Form of Supplement and Addition of Ionophore Effects on Steer Performance while Grazing Bromegrass and Subsequent Effects in Feedlot and Carcass Measures - J. K. Farney; K. Malone (Kansas Agricultural Experiment Station Research Reports, 2021)
Stocker steers were grazed on bromegrass from April to the end of August and were supplemented with several different forms of products. Treatment structure was a 2 × 2 + 2 factorial (six total treatments). Treatments evaluated included mineral only; free-choice supplementation in the form of liquid feed (MIX30) or block format (Mintrate); hand-fed supplement of corn:dried distillers grains at 0.25% of body weight on a dry matter basis offered three times per week; and ionophore (Rumensin) was included in one block and hand-fed supplement. Steers were weighed every 28 days while on grass and in the feedlot. Steers were ultrasounded prior to placement in the feedlot and harvested when they reached at least 0.4-in. backfat and scanned Choice at 115 days on feed. There was no difference in steer gains during the grazing phase or feedlot phase based on all treatments, or if ionophore was included. However, during the grazing period hand-fed steers had greater gain than self-fed supplemented steers and these steers also had more backfat coming off-grass than other supplemented steers. During the finishing phase the steers that were on the self-fed supplement while on grass compensated and had a greater average daily gain than hand-fed steers. Hand-fed supplemented steers tended to have a more backfat at harvest and subsequently higher (but still acceptable) yield grade. Steers that were supplemented with MIX30 tended to have a greater average daily gain (ADG) in the feedlot than hand-fed steers, with block supplemented steers being intermediate. Additionally, MIX30 steers had a heavier final weight prior to harvest than block supplemented steers, with hand-fed being intermediate. There was no difference in ADG or total gain for the entire system (grazing and feedlot period).
Keywords: liquid feed; pressed block; hand-fed; marbling